PENGARUH AUDIT FEE DAN REPUTASI AUDITOR TERHADAP AUDIT DELAY PADA PERUSAHAAN ENERGI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Esti Damayanti, SE., M.Si. (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2022)
The purpose of this research is to determine and analyze that audit fee, and reputation of auditor have an impact on audit delay in energy companies listed on the Indonesian Stock Exchange from 2017  to 2019. This research is a causal comparative with quantitative approach. The samples are 32 energy companies with purposive sampling method. The research was using data that downloaded from official website of Indonesian Stock Exchange. The data analysis techniques are descriptive statistics, precondition analysis test, and hypothesis tests using single and multiple linear regression analysis that tested on IBM SPSS Version 25. The results show audit fee has no impact on audit delay whereas reputation of auditor has negative significant on audit delay. Simultaneously, audit fee and reputation of auditor have significant impact on audit delay.